Acute upper and lower gastrointestinal bleeding management in older people taking or not taking anticoagulants: a literature review - Menichelli, Danilo; Gazzaniga, Gianluca; Del Sole, Francesco; Pani, Arianna; Pignatelli, Pasquale; Pastori, Daniele (Frontiers in Medicine, 2024)
Acute upper and lower gastrointestinal (GI) bleeding may be a potentially life-threatening event that requires prompt recognition and an early effective management, being responsible for a considerable number of hospital admissions. Methods. We perform a clinical review to summarize the recent international guidelines, helping the physician in clinical practice. Older people are a vulnerable subgroup of patients more prone to developing GI bleeding because of several comorbidities and polypharmacy, especially related to an increased use of antiplatelet and anticoagulant drugs. In addition, older patients may have higher peri-procedural risk that should be evaluated. The recent introduction of reversal strategies may help the management of GI bleeding in this subgroup of patients. In this review, we aimed to (1) summarize the epidemiology and risk factors for upper and lower GI bleeding, (2) describe treatment options with a focus on pharmacodynamics and pharmacokinetics of different proton pump inhibitors, and (3) provide an overview of the clinical management with flowcharts for risk stratification and treatment. In conclusion, GI is common in older patients and an early effective management may be helpful in the reduction of several complications.